Difference Poetry Reading Skills Using Interactive Video Learning Media and Power Point Teaching Materials in Grade IV Elementary School Students - Fafa Emilia Rahmatul Haaf; Rida Fironika Kusumadewi; Sari Yustiana (Universitas Pendidikan Indonesia (UPI), 2021)
In this study, a problem was found, namely in Indonesian language learning where the poetry reading skills of fourth grade students at SD Negeri Gebangsari 01 were classified as low both in terms of rhythm, articulation. volume, expression, and kinesics or body movements. This research is a quantitative research that includes a true experimental design with a posttest only control group design type. This study aims to determine differences in poetry reading skills using interactive video learning media and power point teaching materials for fourth grade students at SD Negeri Gebangsari 01. The results of data analysis Independent Sample T-Test hypothesis test proves that there is a difference in terms of Lower and Upper respectively. negative values, namely lower -22.388 and upper -12,128. while Sig (2-tailed) is worth 0.000.